Peripapillary Retinal Nerve Fiber Layer Thickness in Diabetic Retinopathy Patients measured by Optical Coherence Tomography - Sindi Dwijayanti; Arief Kartasasmita; Iwan Sovani; Erwin Iskandar; Rova Virgana; Grimaldi Ihsan (Indonesian Vitreoretinal Society, 2018)
Introduction: Diabetic retinopathy (DR) is a microvascular complication of diabetes and one of the leading causes of blindness. Retinal function loss in diabetic patients is not only caused by microvascular abnormality but also retinal neurodegeneration. Optical coherence tomography (OCT) can detect retinal neural tissue loss caused by diabetes by measuring the retinal nerve fiber layer (RNFL) thickness on the cross-sectional imaging of the retina. This study is to evaluate the changes of peripapillary retinal nerve fiber layer (RNFL) thickness in diabetic retinopathy patients using OCT and compare it to age matched healthy controls. Methods: A cross-sectional study of 16 eyes from 11 diabetic retinopathy patients and 10 eyes from 7 aged matched healthy subjects for control. Patients underwent optic nerve OCT imaging, RNFL thickness was recorded globally (average thickness) and segmented for superior, inferior, nasal, and temporal quadrants Result: There were no significant difference of the average RNFL thickness in diabetic retinopathy group compared to healthy subjects. However, at the nasal quadrant, there were a significant increased thickness of RNFL compared to healthy subject (p value=0.009). Conclusion: Optical coherence tomography can be used to detect neurodegeneration progression in diabetic retinopathy patients by quantitatively measuring the peripapillary RNFL thickness. This can be used as a diagnostic and prognostic factor in cases of DR.